2017
DOI: 10.1371/journal.pone.0186680
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of Chinese version of Adult Carer Quality of Life questionnaire (AC-QoL) in family caregivers of stroke survivors

Abstract: The Adult Carer Quality of Life questionnaire (AC-QoL) is a reliable and valid instrument used to assess the quality of life (QoL) of adult family caregivers. We explored the psychometric properties and tested the reliability and validity of a Chinese version of the AC-QoL with reliability and validity testing in 409 Chinese stroke caregivers. We used item-total correlation and extreme group comparison to do item analysis. To evaluate its reliability, we used a test-retest reliability approach, intraclass corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…The results of CFA suggested that the original factor structure of the HBQOL was not a good fit to the current data; accordingly, a factor structure appropriate for the current data was obtained using PCA. Our findings are similar to those of previous studies that did not confirm the original factor models using CFA in validity tests of the translated instruments [19, 20]. When an instrument is translated from the original language to another language, CFA does not always confirm the appropriateness of the original factor model.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results of CFA suggested that the original factor structure of the HBQOL was not a good fit to the current data; accordingly, a factor structure appropriate for the current data was obtained using PCA. Our findings are similar to those of previous studies that did not confirm the original factor models using CFA in validity tests of the translated instruments [19, 20]. When an instrument is translated from the original language to another language, CFA does not always confirm the appropriateness of the original factor model.…”
Section: Discussionsupporting
confidence: 77%
“…According to previous studies, if the observed original factor structure of an instrument does not fit a new sample well when the instrument is translated and used in another language, PCA may be used to improve the model [19, 20]. An exploratory principal components analysis was performed, using the principal components method with varimax rotation.…”
Section: Methodsmentioning
confidence: 99%
“…CFA was performed to ascertain the goodness of fit of the measurement model of the NWMHQ. The results indicate that the hypothesized model consisting of the original theoretical framework generated through EFA was supported [ 35 ]. The SDS was used to test the criterion correlation validity, and Pearson’s correlation coefficients were calculated for the total scores.…”
Section: Discussionmentioning
confidence: 97%
“…A 5-point Likert scale was used, with 1 being completely none, and 5 being very much, with a total score of 22 to 110 points. The scale has been tested in caregivers of patients with ischemic stroke [13]. The scale has an overall Cronbach's α coefficient of 0.939 and coefficients of 0.813~0.976 for each dimension.…”
Section: Evaluation Methodsmentioning
confidence: 99%